PENGARUH MACAM PENGENCER DAN LAMA PENYIMPANAN PADA SUHU 5oC TERHADAP MOTILITAS, VIABILITAS DAN ABNORMALITAS SPERMATOZOA AYAM KAMPUNG - Rilandana, Dipta; Saleh, Dadang Mulyadi; Nugroho, Aras Prasetiyo (Fakultas Peternakan Universitas Jenderal Soedirman, 2021)
Background. The aim of the study was to determine the interaction between types of diluents (Ringer's lactate, skimmed milk, and andromed) and storage time at 5°C on motility, viability, and abnormalities of kampung rooster spermatozoa. Materials and Methods. The research materials used were 7 kampung rooster aged 1-1.5 years as a spermatozoa producer, chicken feed, battery cage and its equipment, spermatozoa storage glass, a set of tools to test the quality of spermatozoa, and 1 ml syringe. Other materials are fresh spermatozoa from 7 free-range kampung rooster, skim milk, lactated Ringer, andromed, distilled water, microscopes, dropper pipettes, object glass, cover glass, cement box, thoma chamber, hematocrit pipette, 3% NaCl solution, eosin negrosin solution, refrigerator, and microtube. The research design used was a completely randomized design (CRD) with a factorial pattern of 2 factors: the P factor, namely the kind of diluent and the W factor, the time of storage at 5°C through 3 treatments. There were 3 replications in each treatment so that there were 27 experimental units with each treatment consisting of 3 different times. Results. The results showed that the interaction between different kinds of diluent treatments and storage time had a significant effect (P<0.05) on the viability of kampung rooster spermatozoa, while the interaction between treatments of types of diluents and storage time on motility and abnormalities of kampung rooster spermatozoa had no significant effect (P>0.05). ANOVA results had a very significant effect on the type of diluent (P<0.01) on motility, while the abnormal effect was not significant (P>0.05). Storage time had a significant (P<0.05) effect on abnormalities and had no significant (P>0.05) effect on motility. The results showed that the best motility of free-range kampung rooster spermatozoa was produced by Ringer's lactate diluent with storage for 10 minutes (92%). The best viability of kampung rooster spermatozoa was produced by andromed diluent with storage for 370 minutes (96.5%). Furthermore, the lowest abnormality of kampung rooster spermatozoa was produced by skim milk diluent with storage for 190 minutes (8.5%).